The neural correlates of texture perception: A systematic review and activation likelihood estimation meta‐analysis of functional magnetic resonance imaging studies - Jessica Henderson; Tyler Mari; Danielle Hewitt; Alice Newton‐Fenner; Timo Giesbrecht; Alan Marshall; Andrej Stancak; Nicholas Fallon (Brain and Behavior, 2023)
Abstract Introduction Humans use discriminative touch to perceive texture through dynamic interactions with surfaces, activating low‐threshold mechanoreceptors in the skin. It was largely assumed that texture was processed in primary somatosensory regions in the brain; however, imaging studies indicate heterogeneous patterns of brain activity associated with texture processing. Methods To address this, we conducted a coordinate‐based activation likelihood estimation meta‐analysis of 13 functional magnetic resonance imaging studies (comprising 15 experiments contributing 228 participants and 275 foci) selected by a systematic review. Results Concordant activations for texture perception occurred in the left primary somatosensory and motor regions, with bilateral activations in the secondary somatosensory, posterior insula, and premotor and supplementary motor cortices. We also evaluated differences between studies that compared touch processing to non‐haptic control (e.g., rest or visual control) or those that used haptic control (e.g., shape or orientation perception) to specifically investigate texture encoding. Studies employing a haptic control revealed concordance for texture processing only in the left secondary somatosensory cortex. Contrast analyses demonstrated greater concordance of activations in the left primary somatosensory regions and inferior parietal cortex for studies with a non‐haptic control, compared to experiments accounting for other haptic aspects. Conclusion These findings suggest that texture processing may recruit higher order integrative structures, and the secondary somatosensory cortex may play a key role in encoding textural properties. The present study provides unique insight into the neural correlates of texture‐related processing by assessing the influence of non‐textural haptic elements and identifies opportunities for a future research design to understand the neural processing of texture.